Ductal Carcinoma in Situ of the Breast (Springer International Publishing, 2018)
This book provides up-to-date information on all aspects of ductal carcinoma in situ of the breast, including epidemiology, imaging, pathologic and biologic features, interventional diagnostics, nonpalpable lesion localization, and treatment. Surgical procedures are described in detail, covering breast conservation techniques, conservative mastectomies, breast reconstruction options, and axillary surgery. Guidance is provided on how to ensure adequacy of surgical excision and avoid local recurrence when performing breast conservation surgery and how to minimize morbidity from axillary surgery. The role and techniques of partial and whole breast irradiation are described, and the use of adjuvant systemic therapy options, including endocrine therapy and chemotherapy, is explained. A concluding chapter addresses the issue of recurrence and its current management. This book, designed for ease of consultation, will be of value for all involved in the multidisciplinary care of patients with ductal carcinoma in situ of the breast, including surgeons, medical oncologists, pathologists, radiologists, and radiotherapists. .